Weight Loss Is Not the Answer: A Well‐being Solution to the "Obesity Problem". Issue 12 (December 2015) - Logel, Christine; Stinson, Danu Anthony; Brochu, Paula M.
Abstract: Americans have been gaining weight in recent decades, prompting widespread concern about the health implications of this change. Governments, health practitioners, and the general public all want to know: What is the best way to reduce the health risks associated with higher body weight? The dominant weight‐loss solution to this "obesity problem" encourages individuals to lose weight through behavior change. This solution rests on the assumptions that higher body weight causes health problems, that permanent weight loss is attainable, and that weight loss improves health. But comprehensive reviews of the scientific evidence find mixed, weak, and sometimes contradictory evidence for these premises. We suggest that a different solution to the "obesity problem" is needed – a solution that acknowledges both the multifaceted nature of health and the complex interaction between person and situation that characterizes the connection between weight and health. Thus, we use the lens of social psychological science to propose an alternative, well‐being solution to the "obesity problem". This solution has the potential to improve health by encouraging eating and exercising for optimal health rather than weight loss, by developing interventions to reduce weight stigma and discrimination, and by helping higher body‐weight people cope with the stress of stigma and discrimination.